A SURGICAL DECISION-MAKING FRAMEWORK FOR OPTIMAL APPROACHES TO NEPHRECTOMY - A.YU. ODILOV; Z.A. KADYROV; F.S. SADULLOEV (Avicenna Tajik State Medical University, 2024)
Objective: To determine the optimal surgical approach when performing nephrectomy by assessing the main intra- and postoperative indicators of various operative surgical technique types of nephrectomy. Methods: A total of 803 patients underwent examination and surgery for various conditions accompanied by renal failure, such as urolithiasis, pyonephrosis, pyelonephritis, obstructive uropathy with nephrosclerosis, and large or difficult-to-reach kidney tumors. A conventional open nephrectomy (ON) and laparoscopic nephrectomy (LN) using various as well as retroperitoneoscopic nephrectomy (RN) were performed in 368, 269, and 166 cases, respectively Results: The average duration of LN, RN, and ON was 140.0 minutes (range 40-420 minutes), 120.0 minutes (range 40-220 minutes), and 95.0 minutes (range 35-290 minutes), respectively (p<0.001). The proposed tactics using retroperitoneoscopic access helped to reduce the average operation time by 32.23 minutes. In patients with a history of lumbar surgery, laparoscopic access reduced operation time by 1.2 times (23.20 minutes). In large tumors in the anterior segment that have invaded the renal sinus, using RN reduced operation time by 23.01 minutes. Similarly, in tumors in the posterior segment that have invaded the sinus, using LN reduced operation time by 23.40 minutes. Our improved one-stage nephrectomy method for pyonephrosis has reduced the length of hospital stay compared to the two-stage method. We recorded statistically significant differences in the number of blood transfusions, length of stay in intensive care, usage of analgesics (both narcotic and non-narcotic), and number of days of postoperative stays for ON and videoendoscopic nephrectomy methods. Conclusion: Our findings suggest implementing a case-based surgical approach during nephrectomy is feasible and effective. The choice of access should be made based on the specific clinical situation. Despite the long duration of the operation, videoendoscopic methods have clear advantages over conventional ones in terms of such parameters as the volume of blood loss, postoperative analgesia, length of stay in the intensive care unit, and hospital stay overall.